Review Artikel: Validasi Metode Analisis Penetapan Kadar Parasetamol Dalam Sampel Biologis Dengan Berbagai Metode - Tiwi Ambarati; Najla Yusiana Wahyudi; Saarah Hamidah Asmara Indratno; lina Nurfadhila; Marsah Rahmawati Utami (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Paracetamol is one of the most widely used pain relievers and analgesic drugs by the public. Examination of drug concentrations in biological samples using appropriate methods is necessary to ensure drug quality and optimize drug therapy. Therefore, this literature study was conducted with the aim of determining paracetamol levels in biological samples and testing its validity with various methods. Literature research was carried out by searching for several research journal articles that had been published in 2013-2023, which were selected according to the inclusion and exclusion criteria. Six journals were obtained regarding the validation of analytical methods for determining paracetamol levels in biological samples using various methods such as Gas Chromatography-Mass Spectrometry (GC-MS), Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS), Mass Spectrometry-High Performance Liquid Chromatography (HPLC- MS), and Mass Spectrometry Ultra High-Performance Liquid Chromatography (UHPLC-MS). From the above review it can be concluded that the method of analyzing paracetamol compounds in biological samples can be carried out with these four methods where the results of the analytical methods namely accuracy, selectivity, linearity, precision, LOD, and LOQ all meet the requirements or set criteria.